Adding value to smallholder forage-based dual-purpose cattle value chains in Nicaragua, in the context of carbon insetting. Thesis (MSc. in Agricultural Sciences in the Tropics and Subtropics) - Phelan, Lisette Tara (University of Hohenheim, 2015)
The thesis explores the extent to which payment for the ecosystem service of carbon sequestration provided in a value chain context, through an innovative climate change mitigation and adaptation strategy known as 'carbon insetting', could generate 'win-win' outcomes for all actors.